(untitled) (Emancipação, 2026)
This article stems from the need to study public health policies in the prison context, focusing on incarcerated drug users, based on the model proposed by the Advocacy Coalition Framework (ACF). Thus, this study aims to identify the distinct positions within the subsystem that consider the relationship between drugs and the prison system. To achieve this, this research involved content analysis of documents and statements produced by actors in the Executive, Legislative, and Judiciary branches, as well as members of civil society interested in the topic. In addition to identifying the coalitions, this document proposes a belief system for each, taking into account the hard, political, and instrumental aspects. Among the findings there is the presence of five advocacy coalitions in the subsystem that are formed based on their own beliefs, which are not necessarily antagonistic to each other. Furthermore, they demonstrated that coalitions that consider health policies appear less frequently and have fewer engaged actors than the ones that start from the logic of public security or the legal apparatus.